Greek mythology - Selby, Mabelle (My University, 1895)
Introduction: What is Mythology? Webster defines it as “a system of fables—or a treatise upon fables—the collective body of traditions of any heathen nation respecting its gods and other fabulous, supernatural being.” These traditions differ from an allegory in that they are spontaneous, not reflective. It is characteristic of a myth that nobody knows when, where or under what conditions it originated. A myth and a mere story are discriminated by the fact that a myth is allied to a certain, although now antiquated, bit of history. It is a story which, when deprived of its clothing and ornamentation and left bare, becomes a fact in the history of remote ages. It is poetical as well as historical and may be either credible or incredible. Some one has said of the ancients that “where we have recourse to a scientific theorem, they were contented with a myth.” To the Greeks nature overflowed with deities. Every stream had its protecting god—every fountain its presiding nymph—every grove and forest was the home of some deity that the Greeks loved as ardently as they did their nearest friends.
Citation: Selby, Mabelle. Greek mythology. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Mythology; Greek mythology; Theses; Manuscripts (documents)